The 2nd International Cell Death Research Congress 2018
DOI: 10.3390/proceedings2251528
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamic Acids in Wild Blueberry and Effects of Hydroxycinnamic Acids on Apoptosis Induction in Cancer Cell Culture

Abstract: In this study, the fruits and leaves of wild blueberries grown naturally in our country will be evaluated by using different infusion and boiling methods. Blueberry teas; leaves, raw fruit, dried and shredded raw fruit, fruit beans and seedless raw fruit of different infusions were used after boiling them for 1 min, 3 min, 5 min, 7 min, 10 min. Phenolic levels were determined by LC MS/MS technique. The antioxidant and activities of all products in the vitro HCT-116 colon cancer cell line were analyzed by spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a study regarding the effects of bilberry on cancer cell lines, Durmaz et al [67] found an IC 50 value of 0.0291 mg/mL for caffeic acid, 0.0399 mg/mL for p-coumaric acid, and 0.239 mg/mL for ferulic acid. Choi et al [68] reported that blueberry weakly inhibited diphospho-glucuronosyltransferase, with an IC 50 value of 0.0624 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In a study regarding the effects of bilberry on cancer cell lines, Durmaz et al [67] found an IC 50 value of 0.0291 mg/mL for caffeic acid, 0.0399 mg/mL for p-coumaric acid, and 0.239 mg/mL for ferulic acid. Choi et al [68] reported that blueberry weakly inhibited diphospho-glucuronosyltransferase, with an IC 50 value of 0.0624 mg/mL.…”
Section: Discussionmentioning
confidence: 99%